2020
DOI: 10.3390/su12114554
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Energy Landscapes: A Regional Case Study in the Western Netherlands

Abstract: While the transition to renewable energy becomes a main driver of landscape change, few publications discuss the historical transformation of landscapes for the development of energy—commonly referred to as energy landscape. The research reported in this paper investigates the evolution of energy landscapes in the Western Netherlands—a region shaped by peat extraction and dotted with windmills. Five periods have been identified, dominated by wood, peat, wind, fossil fuels, and modern renewables, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
(66 reference statements)
0
10
0
Order By: Relevance
“…Nikas et al [7] argued that citizen involvement is important for sound, acceptable, and effective policymaking in the process of introducing alternative energy. Jong et al [8] analyzed the historical energy-landscape over time in the Netherlands and showed the trend of change is becoming more dynamic. A survey of residents in the area where an offshore wind farm is planned off Cape Cod found that the majority of the population was concerned about the impact on the natural environment and a much smaller portion of the population expected a positive effect [9].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nikas et al [7] argued that citizen involvement is important for sound, acceptable, and effective policymaking in the process of introducing alternative energy. Jong et al [8] analyzed the historical energy-landscape over time in the Netherlands and showed the trend of change is becoming more dynamic. A survey of residents in the area where an offshore wind farm is planned off Cape Cod found that the majority of the population was concerned about the impact on the natural environment and a much smaller portion of the population expected a positive effect [9].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Europe, large-scale use of peat for fuel started in the Middle Ages (1000 to 1500 AD) [1]. In the Western Netherlands, peat extraction initially aimed to clear wetlands for settlements and agriculture, while the extracted peat was used as a fuel to replace the shortfall in wood fuel due to widespread deforestation [1]. However, by the seventeenth century, peat had become a major national energy source in The Netherlands [11].…”
Section: Peat Extraction For Energy (A) Global Extent Of Peat Extraction For Energymentioning
confidence: 99%
“…Soils have both direct and indirect impacts on available energy, but methods used to provide energy, in themselves, have direct and indirect impacts on soils. These impacts can influence the evolution of the landscape and ecosystem services provided by soils [1]. This occurs through four different processes associated with energy provision; acquisition of the energy source, conversion/storage, transport/ transmission and end use/disposal of residues from the energy conversion process [2].…”
Section: Introductionmentioning
confidence: 99%
“…This method allowed to study the direction of landscape changes along with the time analysis. The transformation of landscape under the influence of human activity over the centuries with the use of Geographic Information System, was also studied by De Jong and Stremke [2020]. The article presents a case study that aimed to map the evolution of energy landscapes in the region of the western part of the Netherlands.…”
Section: Introductionmentioning
confidence: 99%